IJBSM Editorial - . (International Journal of Bio-resource and Stress Management, 2010)
The world’s greatest concentration of biological wealth is found in tropical developing countries that are beset by acute poverty. Biological diversity comprises countless plants that feed and heal people, many crop varieties and aquatic species with specific nutritional characteristics, livestock species adapted to harsh environments, insects that pollinate fields and micro-organisms that regenerate agricultural soils. Biodiversity, essential for agriculture and food production, is threatened by urbanization, deforestation, pollution and the conversion of wetlands. This poses a great threat to the security of human beings….